New Paradigm: Coal Fly Ash as the Main Cause of Stratospheric Ozone Depletion - Whiteside, Mark; Herndon, J. Marvin (European Journal of Applied Sciences, 2022)
We provide further compelling evidence that aerosolized coal fly ash and its various components, especially iron, is the primary cause of stratospheric ozone depletion, not chlorofluorocarbon (CFC) gases, as “decreed” by the Montreal Protocol of 1989. Aerosolized coal fly ash is a toxic “witches’ brew” of numerous elements and substances that destroy ozone directly and indirectly by numerous chemical reactions, the full extent of which is not yet known. The prevailing CFC-ozone depletion theory is simply wrong, and does not account for multiple chemical and photochemical reactions that kill stratospheric ozone. We discuss the primary role of coal fly ash particles in ice nucleation and cloud formation in the upper troposphere and stratosphere, and dispel the notion that meteoric or extra-terrestrial material is responsible for polar stratospheric clouds. We provide extensive documentation that iron and several other elements found in coal fly ash are trapped in polar stratospheric clouds and destroy ozone by various means, especially when they are released in the spring. Recent scientific discoveries “fit together” to strongly support the New Paradigm of stratospheric ozone depletion by coal fly ash. The “World Not Avoided” by the Montreal Protocol is already here: The biosphere is in collapse with runaway global warming, and lethal ultraviolet radiation penetrating to Earth’s surface. This new paradigm shift must be operationalized. Time is critically short to salvage what we can of Earth’s vital life support systems, including the stratospheric ozone layer. We reiterate that all sources of aerosolized coal fly ash must be reduced and/or eliminated. All forms of geoengineering must stop immediately if we are to survive as a species. The deliberate assault on Earth’s natural processes, we allege, constitutes no less than acts of planetary treason.